Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Enhancing power-to-hydrogen efficiency: A streamline-shaped flow channel design for alkaline water electrolyzers verified using a microfluidic experimental platform - Xiudong Duan; Ziyu Liu; Ang Lu; Jiachang Wan; Fan Chen; Desheng Li; Xiaomeng Ai; Chaolong Song; Jiakun Fang (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Preparation and Adsorption Performance of Composite Activated Carbon from Organic Sludge and Biomass - Suqing Lu; Ang Wang; Yin Li; Yanqin Guo; Hanqiao Liu (Water, Air, & Soil Pollution, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Flash Joule carbothermal chemistry to synthesize porous silica-based ceramics for thermal safety - Feng Xu; Hongjian Zhang; Edison Huixiang Ang; Yisha Wang; Tianyang Cui; Yufei Lu; Zhentao Nie; Haoyang Wang; Wei Yang; Jixin Zhu (Chemical Engineering Journal, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

An integrated meteorological adaptive simulation-optimization framework for real-time irrigation scheduling considering perfect weather forecasts - Kexin Li; Yanan Jiang; Ang Li; Xiangzhe Tian; Jiatong Lu; Tingting Wei; Jiangfeng Xiangli; Xifeng Huang; Yongmin Li; Shikun Sun (Agricultural Systems, 2026)

Isolation, characterization, and anti-neuroinflammatory activity of sesquiterpenoids from Pogostemon esquirolii - Yebi Qin; Xinyan Shao; Yinzheng Xie; Hailin Lu; Kaien Chen; Xi Zheng; Guodong Chen; Lishe Gan; Song Ang; Dongli Li (Phytochemistry, 2026)

Carbon Fiber-based supercapacitor with cellulose gel electrolyte - Luxin Fang; Miaoqian Zhang; Bo Duan; Ang Lu (Chemical Engineering Journal, 2025)

Fully exposed Fe clusters activated with interfacial oxygen vacancy for accelerating catalytic ozonation of electron-deficient 1-adamantanecaboxylic acid through interfacial electronic metal-support interactions - Xuan Qu; Lu Wang; Zhi-Qiang Sun; Ang Li; Jun Ma (Chemical Engineering Journal, 2025)

Biochar-mediated electron transfer in a spinel ferrite catalyst boosts peracetic acid activation for water decontamination - Lu Xia; Xinlan Li; Zhuojun Wei; Ang Liu; Jianqiu Chen; Jingge Shang (Chemical Engineering Journal, 2025)

Acetylated glucomannan-CNT scaffolds with dual-drug release promote hiPSCs-driven cortical regeneration by suppressing inflammation and anoikis - Yue Gao; Wenxi Li; Wanting Lu; Fuqiang Tang; Xian Xiao; Yinggang Li; Jiaxing Huang; Zhiqi Liang; Yuqing Wu; Yanwen Li; Qingjian Zou; Liangxue Lai; et al. (Carbohydrate Polymers, 2025)

Chemical analysis of mulberry (Morus alba L.) leaves treated with jasmonates on nutrition composition and biological activity - Zhi-Ang Zhang; Jia-Ying Liu; Jia-Le Tian; Marriam Khurshid; Cheng-Hai Yan; Richard Ansah Herman; Lu-Chan Gong; Jun Wang (Food Chemistry, 2025)

Association between per- and polyfluoroalkyl substances with serum hepatobiliary system function biomarkers in patients with acute coronary syndrome - Fang Xiao; Ming Yang; Junli Lv; Jing Li; Mingmei Guo; WenJing Duan; Haoran Li; Ziwen An; Zhengyi Su; Ang Li; Yi Liu; Jingchao Lu; et al. (Journal of Environmental Sciences, 2025)

Revealing the ionic storage mechanisms of Mo2VC2Tz (MXene) in multiple aqueous electrolytes for high-performance supercapacitors - Xiaodie Xuan; Yangyang Xie; Yi Tang; Jianghong Zhou; Zhao Bi; Junhui Zou; Yu-ang Lei; Jiahang Gao; Lu Li; Aibo Zhang; Chenhui Yang (Chemical Engineering Journal, 2025)

Bioinspired anisotropic cellulose evaporator for high-efficiency solar interfacial desalination - Kuankuan Shen; Miaoqian Zhang; Xinyuan Cheng; Xujie Du; Yixiang Wang; Ang Lu (Chemical Engineering Journal, 2025)

Study on short-term total hardness prediction of water quality based on CNN-BiLSTM-SA model: A case study of Henan Province - Huan Xu; Hehu Zhang; Youwei Wang; Lingling Lu; Ang Wu; Ying Chen; Yahui Li; Chuanxin Dong; Xiushan Wang (Journal of Water Process Engineering, 2025)

Degradation of o-DCB and dioxins by MnCe catalysts prepared via the mechanochemical method - Fan Yao; Yaqi Peng; Zhiyuan Gong; Ling Wang; Hongxian Li; Qi Liu; Guanjie Wang; Minghui Tang; Ang Cao; Shengyong Lu (Journal of Environmental Chemical Engineering, 2025)

Transforming waste into value: Efficient recycling of KCl and NH₄F via electrodialysis metathesis - Huimin Ruan; Hao Lu; Jikuan Wang; Jiayun Shi; Zhibo Zhang; Junbin Liao; Edison Huixiang Ang; Jiangnan Shen (Desalination, 2025)

Establishment of molecular weight specific chromatogram of Ganoderma glycopeptide and its application in extract - Hongjian Luo; Shuqian Lin; Zhanxi Lin; Haining Lu; Ang Ma; Dongmei Lin (Food Bioscience, 2025)

Balls-on-ball structured S-scheme heterojunction with localized hotspot effects for boosted photothermal-assisted photocatalytic synthesis of hydrogen - Yu Shen; Jinqi Shi; Jieyu Lei; Pengnian Shan; Ang Bian; Wei Kong; Arkadii Proskurin; Mengtian Wu; Changyu Lu; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2025)

Trait–environmental relationships reveal microbial strategies of environmental adaptation - Minglei Ren; Ang Hu; Zhonghua Zhao; Xiaolong Yao; Ismael Aaron Kimirei; Lu Zhang; Jianjun Wang (Ecology, 2025)
Microbial trait variation along environmental gradients is crucial to understanding their ecological adaptation mechanisms. With the increasing availability of microbial genomes, making full use of the genome‐based traits to decipher their adaptation strategies becomes promising and urgent. Here, we examined microbial communities in water and sediments of 20 East African lakes with pH values ranging from 7.2 to 10.1 through taxonomic profiling and genome‐centric metagenomics. We identified functional traits important for microbial adaptation to the stresses of alkalinity and salinity based on the significant trait–environment relationships (TERs), including those involved in cytoplasmic pH homeostasis, compatible solute accumulation, cell envelope modification, and energy requisition. By integrating these significant traits, we further developed an environmental adaptation index to quantify the species‐level adaptive capacity for environmental stresses, such as high pH environments. The adaptation index of pH showed consistently significant positive relationships with species pH optima across regional and global genomic datasets from freshwater, marine, and soda lake ecosystems. The generality of the index for quantifying environmental adaptation was demonstrated by showing significant relationships with the species niche optima for the gradients of soil temperature and seawater salinity. These results highlight the importance of TERs in facilitating the inference of microbial genomic‐based adaptation mechanisms and expand our understanding of ecological adaptive strategies along environmental gradients.

Salinity impacts on n-alkanes in lake sediments of the Badain Jaran Desert, Northwestern China: Implications for paleoclimate reconstruction - Meng Li; Zhuolun Li; Shipei Dong; Lin Chen; Xianbao Su; Chen'ao Lu; Aifeng Zhou; Nai'ang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Acidic proteomes are linked to microbial alkaline preference in African lakes - Minglei Ren; Ang Hu; Lu Zhang; Xiaolong Yao; Zhonghua Zhao; Ismael Aaron Kimirei; Jianjun Wang (Water Research, 2024)

Formation mechanism and geophysical properties of fracture-filling gas hydrate in the host sediments: A comprehensive review - Gaowei Hu; Zhun Zhang; Yapeng Zhao; Qingtao Bu; Ang Li; Wengao Zhao; Zihao Wang; Xiaoqian Qiu; Tong Liu; Shengbiao Liu; Wanjun Lu; Nengyou Wu (Earth-Science Reviews, 2024)

Boosted photocatalytic H2O2 production in pure water with amino-modified N, S-doped carbon dots - Haoyuan Qin; Lei Sun; Suchang Zou; Ang Bian; Yanhua Cui; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Rational regulation of post-electrodialysis electrochromic anion exchange membranes via TiO2@Ag synergistically strengthens visible-light photocatalytic anti-contamination activity - Yuyang Yao; Yueyue Lu; Jingwen Xu; Jiacheng Yu; Liang Guo; Heda Ding; Jian Li; Junbin Liao; Edison Huixiang Ang; Zhenlu Shen; Jiangnan Shen (Water Research, 2024)

Highly textured CMOS-compatible hexagonal boron nitride-based neuristor for reservoir computing - Haizhong Zhang; Jiayi Li; Xin Ju; Jie Jiang; Jing Wu; Dongzhi Chi; Diing Shenp Ang; Wei Hu; Rongshan Wei; Minmin Zhu; Xiaoqiang Lu (Chemical Engineering Journal, 2024)

Regulation of thermal migration channel in cellulose hydrogel to enhance thermopower - Xinyuan Cheng; Yang Hu; Pan Chen; Haisong Qi; Ang Lu (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Stretchable, adhesive, conductive hydrogel initiated by liquid metal complex for multi-functional sensing - Yuecong Luo; Qiannian Yang; Minzhang Chen; Kaixiang Long; Cuicui Su; Jingxing Li; Mingkun Huang; Ang Lu; Shishang Guo (Chemical Engineering Journal, 2024)

Mulberry (Morus alba L.) leaf powder modified the processing of meat alternatives: Principal component analysis from apparent properties to chemical bonds - Zhi-Ang Zhang; Xiao-Meng Xun; Richard Ansah Herman; Zhan-Peng Zhang; Cheng-Hai Yan; Lu-Chan Gong; Jun Wang (Food Chemistry, 2024)

Ultrafast hot electron transfer and trap-state mediated charge separation for boosted photothermal-assisted photocatalytic H2 evolution - Hao Yuan; Haoyuan Qin; Kaiqu Sun; Xinhai Sun; Jialin Lu; Ang Bian; Jianhua Hou; Changyu Lu; Chunsheng Li; Feng Guo; Weilong Shi (Chemical Engineering Journal, 2024)

Local spin-state tuning enables high-efficiency nickel sulfide cathode for stable alkaline Zn batteries - Ang Yi; Lijun Zhou; Jinhao Xie; Xin Shi; Hui Liang; Fuxin Wang; Dezhou Zheng; Xihong Lu (Chemical Engineering Journal, 2024)

Elucidating the unexpected importance of intermediate-volatility organic compounds (IVOCs) from refueling procedure - Xinping Yang; Kai Song; Song Guo; Yunjing Wang; Junfang Wang; Di Peng; Yi Wen; Ang Li; Baoming Fan; Sihua Lu; Yan Ding (Journal of Hazardous Materials, 2024)

Chitin nanofibrils assisted 3D printing all-chitin hydrogels for wound dressing - Yiran Zheng; Hao Zhang; Zhiwei Wang; Ang Lu; Aixi Yu; Bo Duan (Carbohydrate Polymers, 2024)

Bioinspired wet adhesive carboxymethyl cellulose-based hydrogel with rapid shape adaptability and antioxidant activity for diabetic wound repair - Hongxia Xie; Ge Shi; Ruizi Wang; Xueyu Jiang; Qianqian Chen; Aixi Yu; Ang Lu (Carbohydrate Polymers, 2024)

Carbon sequestration potential of biochar in soil from the perspective of organic carbon structural modification - Lanfang Han; Cuiling Lu; Liying Chen; Fayuan Wang; Qi’ang Chen; Kuo Gao; Yuanyuan Yu; Chao Xu (Applied Soil Ecology, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

Innovative sodium acrylate wastewater resource recovery through electrodialysis with integrated bipolar membranes - Hailong Cui; Huimin Ruan; Haili Wei; Edison Huixiang Ang; Yudi Dong; Hao Lu; Hongyu Liu; Junbin Liao; Yanqing Xu; Jiangnan Shen (Journal of Environmental Chemical Engineering, 2024)

Spawning, larval morphological ontogeny and first feeding of yellow-striped cardinalfish Ostorhinchus cyanosoma (Bleeker, 1853) - Ang Lu; Xiang-Yu Li; Yi-Yang Lin; Yen-Ju Pan (Aquaculture, 2024)

Design and fabrication of self-suspending aluminum-plastic/semiconductor photocatalyst devices for solar energy conversion - Zhi-Ang Zhao; Jingyun Mao; Chengjing Lu; Shuangqiao Yang; Qingrong Qian; Qinghua Chen; Hun Xue; Xiaoli Sun; Min-Quan Yang (Journal of Environmental Sciences, 2024)

Eco-infused interfacial enhancement of the anti-biofouling activity in anion exchange membranes for electrodialysis desalination - Yuyang Yao; Yueyue Lu; Yuan Li; Yanjing Ma; Edison Huixiang Ang; Jingwen Xu; Heda Ding; Yuna Shi; Yitao Chen; Junbin Liao; Zhenlu Shen; Jiangnan Shen (Chemical Engineering Journal, 2024)

Particle-bound reactive oxygen species in cooking emissions: Aging effects and cytotoxicity - Lu Lu; Vanessa Y.Z. Ng; Melvyn Z.H. Tan; Nethmi Y. Kasthuriarachchi; Laura-Helena Rivellini; Yue Qian Tan; Lina Ang; Maximillian Viera; Boon Huat Bay; Wei Jie Seow; Alex K.Y. Lee (Atmospheric Environment, 2024)

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

Multi-omics analyses reveal relationships among polyphenol-rich oolong tea consumption, gut microbiota, and metabolic profile: A pilot study - Ang Li; Ruixin Kou; Haiwei Liu; Mengshan Chen; Jin Wang; Qisijing Liu; Xiaolong Xing; Bowei Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2023)

Generation estimation and metals recycling potentials evaluation of retired mobile phones in Korea - Ang Li; Bo Li; Huibin Wang; Xia Liu; Yanan Guo; Bin Lu (Environmental Science and Pollution Research, 2023)

Exposure to cooking fumes is associated with perturbations in nasal microbiota composition: A pilot study - Xin Er Frances Jin; Dorrain Yanwen Low; Lina Ang; Lu Lu; Xin Yin; Yue Qian Tan; Alex King Yin Lee; Wei Jie Seow (Environmental Research, 2023)

Experimental and numerical tests on shear failure and size effect of CFRP-wrapped RC beams without stirrups: Influence of the shear-span ratio - Xuan'ang Jiang; Liu Jin; Kai Lu; Xiuli Du (Engineering Structures, 2023)

Correction to: Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Investigation of dynamic crack formation mechanism based on a new crack dynamic driving model - Xiao Liu; Peng Yan; Wenbo Lu; Jin Zhu; Xiangyu Zhang; Ang Lu; Ming Chen; Gaohui Wang (Computers and Geotechnics, 2023)

The thermodynamics of enhanced dope stability of cellulose solution in NaOH solution by urea - Yu Chen; Yoshiharu Nishiyama; Ang Lu; Yan Fang; Ziqiang Shao; Tao Hu; Dongdong Ye; Haisong Qi; Xiaodong Li; Jakob Wohlert; Pan Chen (Carbohydrate Polymers, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Palaeoenvironmental evolution of the Badain Jaran Desert hinterland during the Early to Middle Holocene: A multi-proxy reconstruction on Taoerlegetu paleolake, northwest China - Chen’ao Lu; Nai'’ang Wang; Lvlv Zhang; Zhuolun Li; Wenwei Zhao; Meng Li; Xianbao Su; Yixin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Soil moisture–atmosphere feedback dominates land N 2 O nitrification emissions and denitrification reduction - Jiayuan Liao; Qiqi Luo; Ang Hu; Wenkai Wan; Dian Tian; Jingwei Ma; Tian Ma; Hao Luo; Sheng Lu (Global Change Biology, 2022)
Soil moisture (SM) is essential to microbial nitrogen (N)‐cycling networks in terrestrial ecosystems. Studies have found that SM–atmosphere feedbacks dominate the changes in land carbon fluxes. However, the influence of SM–atmosphere feedbacks on the N fluxes changes, and the underlying mechanisms remain highly unsure, leading to uncertainties in climate projections. To fill this gap, we used in situ observation coupled with gridded and remote sensing data to analyze N 2 O fluxes emissions globally. Here, we investigated the synergistic effects of temperature, hydroclimate on global N 2 O fluxes, as the result of SM–atmosphere feedback impact on N fluxes. We found that SM–temperature feedback dominates land N 2 O emissions by controlling the balance between nitrifier and denitrifier genes. The mechanism is that atmospheric water demand increases with temperature and thereby reduces SM, which increases the dominant N 2 O production nitrifier (containing amoA AOB gene) and decreases the N 2 O consumption denitrifier (containing the nosZ gene), consequently will potential increasing N 2 O emissions. However, we find that the spatial variations of soil–water availability as a result of the nonlinear response of SM to vapor pressure deficit caused by temperature are some of the greatest challenges in predicting future N 2 O emissions. Our data‐driven assessment deepens the understanding of the impact of SM–atmosphere interactions on the soil N cycle, which remains uncertain in earth system models. We suggest that the model needs to account for feedback between SM and atmospheric temperature when estimating the response of the N 2 O emissions to climatic change globally, as well as when conducting field‐scale investigations of the response of the ecosystem to warming.

Generation estimation and material flow analysis of retired mobile phones in China - Ang Li; Bo Li; Bin Lu; Dong Yang; Suxia Hou; Xiaolong Song (Environmental Science and Pollution Research, 2022)

Roles of neutrophil reactive oxygen species (ROS) generation in organ function impairment in sepsis - Jiaqi Lu; Jingyuan Liu; Ang Li (Journal of Zhejiang University-SCIENCE B, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effect of confining pressure on peak penetration force of the TBM disc cutter - Wu Li; Peng Yan; Ang Lu; Shuling Huang; Wenbo Lu (Arabian Journal of Geosciences, 2022)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

OP16 induces deadly autophagy and apoptosis of cells by inhibiting Akt in esophageal squamous cell carcinoma - Guiqin Hou; Ang Jia; Li Yang; Yu Zhao; Yi Hu; Wuduo Zhao; Wen Zhao; Hong-Min Liu; Zhaoming Lu (Molecular and Cellular Biochemistry, 2020)

Enhanced adsorption performance and regeneration of magnetic Fe3O4 nanoparticles assisted extracellular polymeric substances in sulfonamide-contaminated water - Shanshan Pi; Ang Li; Di Cui; Zhou Su; Lu Zhou; Fang Ma (Environmental Science and Pollution Research, 2020)

The mediated role of complement C3 in PM2.5 exposure and type 2 diabetes mellitus: an elderly panel study in Beijing, China - Yuanren Tong; Lu Pei; Kai Luo; Meiduo Zhao; Jing Xu; Ang Li; Runkui Li; Mingan Yang; Qun Xu (Environmental Science and Pollution Research, 2019)

Spatial variation in the effects of air pollution on cardiovascular mortality in Beijing, China - Wenjing Li; Lu Pei; Ang Li; Kai Luo; Yang Cao; Runkui Li; Qun Xu (Environmental Science and Pollution Research, 2019)

Conversion of phosphatidylinositol (PI) to PI4‐phosphate (PI4P) and then to PI(4,5)P 2 is essential for the cytosolic Ca 2+ concentration under heat stress in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2018)
Summary How cells drive the phospholipid signal response to heat stress (HS) to maintain cellular homeostasis is a fundamental issue in biology, but the regulatory mechanism of this fundamental process is unclear. Previous quantitative analyses of lipids showed that phosphatidylinositol (PI) accumulates after HS in Ganoderma lucidum , implying the inositol phospholipid signal may be associated with HS signal transduction. Here, we found that the PI‐4‐kinase and PI‐4‐phosphate‐5‐kinase activities are activated and that their lipid products PI‐4‐phosphate and PI‐4,5‐bisphosphate are increased under HS. Further experimental results showed that the cytosolic Ca 2+ ([Ca 2+ ] c ) and ganoderic acid (GA) contents induced by HS were decreased when cells were pretreated with Li + , an inhibitor of inositol monophosphatase, and this decrease could be rescued by PI and PI‐4‐phosphate. Furthermore, inhibition of PI‐4‐kinases resulted in a decrease in the Ca 2+ and GA contents under HS that could be rescued by PI‐4‐phosphate but not PI. However, the decrease in the Ca 2+ and GA contents by silencing of PI‐4‐phosphate‐5‐kinase could not be rescued by PI‐4‐phosphate. Taken together, our study reveals the essential role of the step converting PI to PI‐4‐phosphate and then to PI‐4,5‐bisphosphate in [Ca 2+ ] c signalling and GA biosynthesis under HS.

Phospholipase D and phosphatidic acid mediate heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Xiao‐Xiao Lu; Dai Chen; Ya‐Ping Lu; Ang Ren; Liang Shi; Jing Zhu; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Phospholipid‐mediated signal transduction plays a key role in responses to environmental changes, but little is known about the role of phospholipid signalling in microorganisms. Heat stress (HS) is one of the most important environmental factors. Our previous study found that HS could induce the biosynthesis of the secondary metabolites, ganoderic acids (GA). Here, we performed a comprehensive mass spectrometry‐based analysis to investigate HS‐induced lipid remodelling in Ganoderma lucidum . In particular, we observed a significant accumulation of phosphatidic acid (PA) on HS. Further genetic tests in which pld ‐silencing strains were constructed demonstrated that the accumulation of PA is dependent on HS‐activated phospholipase D (PLD) hydrolysing phosphatidylethanolamine. Furthermore, we determined the role of PLD and PA in HS‐induced secondary metabolism in G . lucidum . Exogenous 1‐butanol, which decreased PLD‐mediated formation of PA, reverses the increased GA biosynthesis that was elicited by HS. The pld ‐silenced strains partly blocked HS‐induced GA biosynthesis, and this block can be reversed by adding PA. Taken together, our results suggest that PLD and PA are involved in the regulation of HS‐induced secondary metabolism in G . lucidum . Our findings provide key insights into how microorganisms respond to heat stress and then consequently accumulate secondary metabolites by phospholipid remodelling.

Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Tian‐Jun Zhang; Xiao‐Xiao Lu; Bao‐Liang Ma; Ang Ren; Liang Shi; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

Changes in soil organic carbon and total nitrogen stocks after conversion of meadow to cropland in Northeast China - Fan Ding; Ya-Lin Hu; Lu-Jun Li; Ang Li; Shengwei Shi; Pei-Yong Lian; De-Hui Zeng (Plant and Soil, 2013)

Effects of Selenium Source and Level on Growth Performance, Tissue Selenium Concentrations, Antioxidation, and Immune Functions of Heat-Stressed Broilers - Xiudong Liao; Lin Lu; Sufen Li; Songbai Liu; Liyang Zhang; Guangying Wang; Ang Li; Xugang Luo (Biological Trace Element Research, 2012)

Isolation of a cinnamoyl CoA reductase gene involved in formation of stone cells in pear (Pyrus pyrifolia) - Xiao-Peng Lu; Yong-Zhong Liu; Ji-Cui An; Hong-Ju Hu; Shu-Ang Peng (Acta Physiologiae Plantarum, 2011)

Early development of germlings of Sargassum thunbergii (Fucales, Phaeophyta) under laboratory conditions - Ziguo Zhao; Fengjuan Zhao; Jianting Yao; Jingmei Lu; Put. O. Ang; Delin Duan (Journal of Applied Phycology, 2008)

Determination of reduction potential of an engineered CuA azurin by cyclic voltammetry and spectrochemical titrations - Hee Jung Hwang; Majorie Ang; Yi Lu (JBIC Journal of Biological Inorganic Chemistry, 2004)